Perancangan Peralatan Listrik Dengan Voice Control Menggunakan Switch Relay Dan Arduino - Kurnia, Okto (Journal of Information and Technology, 2025)
The work environment has a huge impact on employee satisfaction, productivity, and development. Creating comfortable conditions for employees through a work environment based on smart technology is necessary. The concept of controlling electrical equipment based on voice commands makes it easier for employees to control electrical systems. Allows employees to control electronic devices just by using voice commands without having to move around to turn on or turn off electronic equipment. The main goal of voice command technology is to create a technique and system for entering voice commands into machines, so that machines can understand what humans say and obey what they command. This research will utilize voice recognition technology to control electrical equipment connected to Arduino so that it can be tested for the strength of voice commands to control electronic devices.